UNDERSTANDING MEANING OF POETRY USING GRAMMAR ANALYSIS - Muhammad Saibani Wiyanto (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2014)
This article deals with literary work especially about grammar analysis used to understand meaning poetry by Jo Shapcott. The main point of learning literary is to get some information about life and human being, especially for the expression of feeling through the author of the poem that is Jo Shapcott , and also the distribution of.grammar in poetry of Jo Shapcott. This article focused on grammatical sense in poetry, grammar strictly and universally applied in various literary contexts, and effects to the word meaning of poetry by Jo Shapchott.The article uses structural approach, qualitative descriptive, where the approach is limited on research of the literary work by itself and it is something dependent. It had taken the data to analyze, which is the poems of Jo Shapchott from the library. The instrument used here is human instrument because the researcher acts as the organizer of the research and also the only instrument to collect the data.The result shown that in the poems of Jo Shapcott entitled Hubei Province Tornado could be found the grammatical sense inside the poem. In another poem entitled Station Bookstand that grammar is not bound to follow the strict formulation of the grammatical structure. Then, finding that grammar gives effect to word meaning of poetry by Jo Shapcott